The pooled estimate of the total fertility rate in sub-Saharan Africa using recent (2010–2018) Demographic and Health Survey data - Tesfa, Desalegn; Tiruneh, Sofonyas Abebaw; Gebremariam, Alemayehu Digssie; Azanaw, Melkalem Mamuye; Engidaw, Melaku Tadege; Kefale, Belayneh; Abebe, Bedilu; Dessalegn, Tsion; Tiruneh, Mulu (Frontiers in Public Health, 2023)
Background: Even though the total fertility rate (TFR) has been fallen markedly over recent decades in many countries, the decrement is in steady-state in Sub-Saharan Africa Countries (SSA). However, there is a variation among the sub-regions and inhabitants. This study aimed to undertake a meta-analysis of demographic and health surveys (DHS) to estimate the pooled level of TFR in SSA and to depict Sub-regional and inhabitant differences. Methods: The data source of this study was the standard Demographic and Health Survey datasets of 33 Sub-Saharan Africa countries using one dataset www.meaasuredhs.com between 2010 -2018. The point estimate of the total fertility rate with their corresponding standard error in each Sub-Saharan Africa country was estimated using the DHS.rates R package. Using the point estimate of the total fertility rate with their standard error of each country, the pooled estimate of total fertility rate was pooled by metan STATA command. Results: A total of 1,324,466 live births were included in this study. The pooled estimate of the total fertility rate in Sub-Saharan Africa was five children per woman (95% CI: 4.63 – 5.37). Consequently, the pooled estimate of total fertility in urban and rural inhabitants was 3.90 (95% CI: 3.60 – 4.21) and 5.82 (95% CI: 5.43 – 6.21) children per woman respectively. In sub-group analysis: the pooled estimate of the total fertility rate was 4.74, 5.59 ,3.18 and 5.38 children per women in East African, Central Africa , Southern Africa, and West Africa regions respectivly. Low-income countries had a higher total fertility rate of 5.45 followed by lower middle income 4.70 and high middle-income countries 3.80. Conclusions: Total fertility rate in Sub-Saharan Africa was significantly high. Central Africa and the West African region have the highest total fertility rate. Rural inhabitant and low-income countries have the highest fertility rate. Strategies should be designed on this public health issue in Sub-Saharan Africa countries as a whole and particularly in Central and Western African regions and rural inhabitants.